Nucleating and reinforcing effects of nanobiochar on poly(3-hydroxybutyrate-co-3-hydroxhexanoate) bionanocomposites - Yee Foong Ng, Lawrence; Ariffin, Hidayah; Tengku Yasim-Anuar, Tengku Arisyah; Sakata, Megumi; Kawarada, Tomoya; Yoshimura, Osamu; Tsukegi, Takayuki; Afizan Nik Abd Rahman, Nik Mohd; Hassan, Mohd Ali (Royal Society of Chemistry, 2024)
This study promotes the use of nanobiochar (NBC) as an environmentally friendly substitute to conventional fillers to improve various properties of biopolymers such as their mechanical strength, thermal stability and crystallization properties. TGA analysis showed a slight increase in onset thermal degradation temperature of the composites by up to 5 °C with the addition of 4 wt% NBC. Non-isothermal DSC analysis determined that the addition of NBC into PHBHHx increases the crystallization temperature and degree of crystallinity of PHBHHx while isothermal DSC analysis demonstrated higher crystallization rate in PHBHHx/NBC composited by up to 54%. PHBHHx incorporated with NBC also exhibited superior tensile strength and modulus versus neat PHBHHx. Increase in mechanical strength was further proven via DMA where PHBHHx/NBC composites maintained higher storage modulus at higher temperatures when compared to neat PHBHHx. PHBHHx/NBC also exhibited no cytotoxicity effect against HaCat cells. This study demonstrates the ability of biochar to act as both nucleating agents and reinforcing agents in biodegradable polymers such as PHBHHx, which could be suitable for packaging application.